The Contribution of Reading Strategy and Self Efficacy to the Reading Comprehension of College Students - Pritantina Yuni Lestari (EDUCATION AND LINGUISTICS KNOWLEDGE JOURNAL, 2020)
This research is aimed to know how strong the contribution of readingstrategy and self-efficacy to students’ reading comprehension. Quantitativeapproach with correlational research design used in this research. Correlationalresearch design is chosen to find out the contribution of independent to thedependent variable. The population of English Department of Faculty of TeacherTraining and Education of UNISKA Kediri consisting of 240 students werechosen as the subject of research and 150 of them were selected as the sample.Simple random sampling using lottery was used as the method of taking sample.The data was gotten by applying three instruments, questionnaire for readingstrategy and self-efficacy, especially for self-regulated learning of reading subject,and also reading comprehension test. Then regression formula was used to analysethe contribution of reading strategies and self-efficacy to reading comprehensionof the students.The result states the reading strategy and self-efficacy significantlycontribute to the students’ reading comprehension.